Factors affecting prospective mathematics teachers' beliefs about geometric habits of mind - Buket Özüm Bülbül (Journal of Pedagogical Research, 2021)
This study examined the effect of affective factors, the gender variable, grade level and academic achievement on prospective teachers' (PTs) beliefs about geometric habits of mind. For this purpose, The Belief Scale for geometric habits of mind, Geometry Self-efficacy Scale, Geometry Attitude Scale and a Demographic Characteristics Form were applied to 264 PTs. The data were analyzed using the correlational survey technique. As a result of the study, a significant positive relationship was found between the PTs' self-efficacy regarding geometry and their academic achievements, and their beliefs about geometric habits of mind, Additionally a negative, moderate and significant relationship was found between the attitudes of the PTs towards geometry and their beliefs about geometric habits of mind. Finally, no significant difference was found between the scores of the PTs regarding geometric habits of mind and their gender.